Electronic states and optical transitions in a graphene quantum dot in a normal magnetic field - Grujić Marko; Tadić Milan (Serbian Journal of Electrical Engineering, 2011)
An analytical approach using the Dirac-Weyl equation is implemented to obtain the energy spectrum and optical absorption of a circular graphene quantum dot in the presence of an external magnetic field. The results are obtained for the infinite-mass and zigzag boundary conditions. We found that the energy spectra of a dot with zigzag boundary condition exhibit a zero energy band regardless of the value of the magnetic field, while for the infinite mass boundary conditions, the zero energy states appear only for high magnetic fields.